Micropulse cyclophotocoagulation based on a modified protocol of energy parameters in the treatment of patients with end-stage glaucoma - I. E. Ioshin; A. I. Tolchinskaya; A. V. Rakova; I. V. Maksimov; E. A. Beresenko (Российский офтальмологический журнал)
Purpose: to evaluate the effectiveness of transscleral micropulse cyclophotocoagulation (mCPC) in patients with end-stage glaucoma.Material and methods. 38 patients aged 76.6 ± 7.1 years with end-stage refractory glaucoma were examined, revealing subjective complaints, uncompensated IOP at the maximum hypotensive mode, prior multiple surgical interventions. Indications for mCPC to be performed on a SUPRA 810 device (Quantel Medical, France) according to a modified protocol, in which the laser energy flux is 121.8 J/cm2, were determined. In order to prevent postoperative inflammation after mCPC, a combined drug Floas-T® (glucocorticosteroid fluorometholone + tobramycin) was used.Results. A week after mCPC, the hypotensive effect was achieved in all 38 cases. IOP showed a 30.8 % decrease from the baseline. Considering an additional mCPC given to 14 patients, the entire group showed an IOP 22.8 % decrease (from 34.7 to 26.8 ± 2.9 mm Hg, p < 0.05) achieved after an 18 months’ follow-up. The combined drug Floas-T® was found to contribute to a subjective and clinical improvement, revealing no signs of an increased IOP.Conclusion. The use of mCPC in the treatment of patients with repeatedly operated refractory end-stage glaucoma who receive a maximum hypotensive mode should be estimated as a positive measure. The combined drug based on fluoroquinolone and tobramycin has demonstrated high effectiveness of anti-inflammatory prevention. A survey showed a subjective improvement in the patients’ quality of life. The mCPC method can be recommended as one of the components of a comprehensive rehabilitation program for patients with end-stage glaucoma.